2020
DOI: 10.5123/s1679-497420120000100010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Sistema de Vigilância da Tuberculose Drogarresistente, Brasil, 2013-2017*

Abstract: Objective: to evaluate the Brazilian Drug-Resistant Tuberculosis Surveillance System (DRTB-SS). Methods: this was an evaluative study, following Centers for Disease Control and Prevention guidelines, using national data from the Special Tuberculosis Treatment Information System (SITETB), and the Notifiable Diseases Information System (SINAN), from 2013 to 2017. Results: average data completeness was 95%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…These findings may align with global recommendations for increased funding to achieve universal access [13,14]. They also contribute to the approach proposed by the Brazilian Ministry of Health to improve indicators and identify areas for restructuring the expansion of laboratory and diagnostic networks, keeping as a target the eradication of TB in Brazil by 2035 [12,14].…”
Section: Public Health Implicationssupporting
confidence: 67%
“…These findings may align with global recommendations for increased funding to achieve universal access [13,14]. They also contribute to the approach proposed by the Brazilian Ministry of Health to improve indicators and identify areas for restructuring the expansion of laboratory and diagnostic networks, keeping as a target the eradication of TB in Brazil by 2035 [12,14].…”
Section: Public Health Implicationssupporting
confidence: 67%
“…Previous studies suggested that the sensitivity to drug-resistant TB identification is only 46.6% in Brazil 10 . The present study did not intend to calculate the sensitivity, but to quantify the non-detected resistance cases due to a lack of proper technology.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…These findings may align with global recommendations for increased funding to achieve universal access 11,12 . They also contribute to the approach proposed by the Brazilian Ministry of Health to improve indicators, identifying areas for restructuring the expansion of laboratory and diagnostic networks, keeping as a target the eradication of TB in Brazil by 2035 10,12 .…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Currently, eliminating MDR-TB presents a major challenge, as recognized by the WHO, given its critical impact on public health and potential threat it poses to global security and disease prevention. This leads to less efficient therapeutic schemes and is associated with relapses and unfavorable outcomes 7 , 8 , 9 . Additionally, there is limited data on the catastrophic costs incurred by patients with MDR-TB in countries with a high TB burden 10 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%